Spatiotemporal Features of Retinal Waves Instruct the Wiring of the Visual Circuitry - Arroyo, David A.; Feller, Marla B. (Frontiers in Neural Circuits, 2016)
Coordinated spontaneous activity is present in different sensory systems during early stages of development. This activity is thought to play a critical role in the development of sensory representations before the maturation of sensory experience. In the visual system, the mechanisms by which spatiotemporal properties of retinal spontaneous activity, called retinal waves, drive developmental events has been well studied. Recent advancements in pharmacological, genetic, and optogenetic manipulations have provided further understanding of the contribution of specific spatiotemporal properties of retinal waves to eye-specific segregation and retinotopic refinement of retinofugal projections. Here we review some of the recent progress in understanding the role of retinal waves in the early stages of visual system development, prior to the maturation of vision.